말고기 대체수준이 유화형 소시지 품질에 미치는 영향 - 성필남; 이종언; 김진형; 박범영; 하경희; 고문석 (Journal of animal science and technology, 2006)
The objective of this study was to evaluate the quality of emulsion-type sausage where part of the pork was substituted with horse meat during manufacturing. Three treatments of sausages were manufactured by replacing pork with 0, 50 and 100% horse meat. After manufacturing, sausages were vacuum-packaged and stored 4℃ for 1 day. An increase in horse meat resulted in higher moisture, protein content, and pH values, and lower fat content of sausage(P<0.05). However, no significant effects were observed on texture characteristics and sensory attributes of sausage. The horse meat sausage had higher K, Fe, Zn, Cu, saturated fatty acid contents than 0% horse meat level. Based on the results, it can be concluded that horse meat can be used as a meat replacer in the manufacture of emulsion-type sausages up to a level of 100%. 소시지의 원료육으로 사용되는 돼지고기를 말고기로 0, 50, 100% 대체하여 소시지 품질을 비교한 결과, 말고기 특성이 소시지 품질에 많은 영향을 미쳤다. 특히, 말고기 함량이 높을수록 지방 함량은 작았으며, 수분 함량과 단백질함량은 높은 경향을 보였다. 또한 말고기 소시지는 pH가 높고, 돈육 소시지 보다 제품색이 붉고, 어두운 특성을 보였다. 하지만 소시지의 조직적 특성과 관능적 특성에서는 돼지고기 소시지와 차이를 보이지 않았으며, 오히려 말고기 소시지가 경도와 탄력성에서는 돼지고기 소시지 보다 높은 편이었다. 미량 광물질 중 K, Fe, Zn, Cu는 말고기 소시지가 돼지고기 소시지 보다 더 함량이 많았으며, P, Na 함량은 돼지고기 소시지에서 높게 나타났다. 지방산 조성에서는 말고기 소시지가 포화지방산 비율이 높고, 불포화지방산 비율이 떨어지는 것으로 나타났다. 이상의 결과를 종합하면 소시지 제조 시 돼지고기를 말고기로 대체하여 만들어진 말고기 소시지는 돼지고기만을 원료로 제조한 소시지에 비하여 품질저하를 보이지 않았으며 오히려, 최근 소비자의 건강지향성 등을 고려할 때 저지방, 미량광물질 강화 등 기능성 소시지 제조가 가능할 것으로 판단되었다.